The Relationship Between Family and Socio-Cultural Support and the Provision of Complementary Foods to Infants Under 6 Months of Age in Tataaran II Subdistrict - Cheryl Virginia Kaparang; Melky Pangemanan; Deviana Pratiwi Munthe; Tika Bela Sari; Jilly Toar; Theo W.E Mautang (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Early introduction of complementary foods (MP-ASI) remains a public health problem. Family and socio-cultural factors play an important role in influencing mothers' decisions to provide complementary foods prematurely. This study aims to analyze the relationship between family and socio-cultural support and the practice of providing complementary foods to infants under 6 months of age in Tataaran II Village. The study used a quantitative method with a cross-sectional design. The sample consisted of 89 mothers with infants aged 0–9 months. The sampling technique was total sampling with data collection through questionnaires distributed directly or via Google Form, then data analysis was carried out using the Chi-Square test. The results showed a significant relationship between family support and the provision of complementary foods (p-value <0.001; p <0.05). In addition, there was also a significant relationship between socio-cultural factors and the provision of complementary foods (p-value <0.001; p <0.05). These findings suggest that family support and sociocultural factors play a significant role in encouraging the practice of introducing complementary foods too early, necessitating more intensive educational efforts regarding the importance of exclusive breastfeeding until the infant is 6 months old.